2020
DOI: 10.1073/pnas.1917518117
|View full text |Cite
|
Sign up to set email alerts
|

Triple oxygen isotope insight into terrestrial pyrite oxidation

Abstract: The mass-independent minor oxygen isotope compositions (Δ′17O) of atmospheric O2andCO2are primarily regulated by their relative partial pressures,pO2/pCO2. Pyrite oxidation during chemical weathering on land consumesO2and generates sulfate that is carried to the ocean by rivers. The Δ′17O values of marine sulfate deposits have thus been proposed to quantitatively track ancient atmospheric conditions. This proxy assumes directO2incorporation into terrestrial pyrite oxidation-derived sulfate, but a mechanistic u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
2
2

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 72 publications
4
29
0
Order By: Relevance
“…8d) formation by the fractionating process of microbial sulfate reduction (Thode et al, 1951;Sim et al, 2011), and could feasibly be 34 S-depleted relative to the sulfide minerals of the HHC. Previous work in the Marsyandi river has shown that SO 4 2derived from FeS 2 oxidation in the TSS reaches δ 34 S values as low as approximately -25‰, consistent with but lower than our minimum estimates of δ 34 S FeS2 in downstream stations (Turchyn et al, 2013;Hemingway et al, 2020).…”
Section: Inversion-constrained Fraction Of Fes 2 -Derived So 4 2and δsupporting
confidence: 91%
See 4 more Smart Citations
“…8d) formation by the fractionating process of microbial sulfate reduction (Thode et al, 1951;Sim et al, 2011), and could feasibly be 34 S-depleted relative to the sulfide minerals of the HHC. Previous work in the Marsyandi river has shown that SO 4 2derived from FeS 2 oxidation in the TSS reaches δ 34 S values as low as approximately -25‰, consistent with but lower than our minimum estimates of δ 34 S FeS2 in downstream stations (Turchyn et al, 2013;Hemingway et al, 2020).…”
Section: Inversion-constrained Fraction Of Fes 2 -Derived So 4 2and δsupporting
confidence: 91%
“…The elevated SO 4 2-/Σ + and low δ 34 S SO4 of samples thus requires an additional source of 34 S-depleted sulfur. As previously suggested for the Langtang River (Bhatt et al, 2000; and shown in the Marsyandi catchment (Turchyn et al, 2013;Hemingway et al, 2020), a likely source of this sulfur is the oxidation of FeS 2 . The oxidation of FeS 2 to H 2 SO 4 and subsequent weathering of minerals could increase river SO 4 2-/Σ + and, depending on the value of δ 34 S FeS2 , decrease δ 34 S SO4 to observed values (Fig.…”
Section: Mixing Relations Require Source Of 34 S-depleted So 4 2-supporting
confidence: 61%
See 3 more Smart Citations